Filtering strategies of Polomolok Water District employees in upward networks - Amorio, Vincent J.
The research was conducted to examine the upward networks of Polomolok Water District (PWD) having 60 employees from the organization as the subjects. This focused on the richness of the channels and the filtering strategies employed including the correlation of the two variables. The primary data of the research were obtained from the answers of 60 PWD employees who were chosen through stratified random sampling to answer the survey. In order to substantiate the results, in-depth interviews were done to three employees. The results were analyzed using the Statistical Package for the Social Sciences (SPSS). Results of the research revealed the face to face communication, including meetings, is the frequently used channel by employees in forwarding messages to their superiors. Bulletin on the other hand, is the least used among available channels. Verbal communication was found to be the richest channel while written, impersonally addressed channels such as the bulletin and newsletter were among the lowest in terms of richness. Further, the most filtering strategy among the PWD employees is embellishing the message or the addition of some details to the message forwarded to the supervisor. The least use is leveling the message or the removal of some details in the original message. Among the channels, only the cellular phone and newsletter are correlated to filtering strategies. The in-depth interviews proved that filtering messages within the organization is inevitable. It gives the employees the chance to keep their good image to their supervisor and maintain confidentiality especially if it doesn?t help, at any cost, the organization. Negative consequences may only come out if organizational issues boil down to personal issues of the employees. The author recommends other researcher related to this phenomenon however it will be better if larger organizations where all upward communication channels are exhausted, are chosen as subjects. This way, there is a higher feasibility of determining the relationship between the channels and the filtering strategies. Informal upward network of an organization is also a possible focus of the study.
Thesis, Undergraduate (BA Communication Arts) -- U. P. in Mindanao
Keywords: Communication Arts -- Speech Communication